A rare case of abdominal pregnancy: diagnostic and therapeutic challenges - Mehta, Nishita A.; Fonseca, Michelle N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Abdominal pregnancy refers to a pregnancy that has implanted in the abdominal cavity, the estimated incidence being 1 per 30,000 births. A 36-year-old primigravida with term pregnancy with fetal demise was referred to us. Examination was suggestive of single foetus of 30 weeks’ gestation with longitudinal lie and cephalic presentation with absent foetal heart sounds. The cervical os was closed, uneffaced. Ultrasound done at 18 weeks’ gestation had reported pregnancy in a bicornuate uterus. Present ultrasound revealed intrauterine foetal demise of 28.4 weeks. Cervical ripening, done using prostaglandins, mechanical dilation with Foley’s catheter and oxytocin, had failed, and thus patient was taken up for surgery. Findings revealed an abdominal pregnancy with a macerated fetus of 1070 grams (severely growth restricted). Placenta was found to be implanted on multiple areas of both small and large intestine and posterior peritoneum. Placenta was left in situ. Postoperative recovery was uneventful. She was given higher antibiotics, 4 doses of tablet mifepristone 200 mg and monitored regularly with ultrasound/ MRI and bHCG which showed slow placental resorption. Conclusion- Abdominal pregnancies, associated with a high maternal and perinatal morbidity and mortality, are diagnosed preoperatively only in 45% of cases. Thus, a high index of suspicion and improvement in diagnosis is the need of the hour. Successful management includes prompt intraoperative recognition and management of the placenta (we advocate leaving the placenta in situ), multidisciplinary approach with involvement of surgeons and interventional radiologists, access to blood products, meticulous postoperative care and close observation during the subsequent delayed reabsorption.